Real-time PCR : current technology and applications - Logan, Julie (Julie M. J.); Edwards, Kirstin (Kirstin J.); Saunders, Nick (Nick A.) (Norfolk, UK : Caister Academic Press, 2009)
"This essential manual presents a comprehensive guide to the most up-to-date technologies and applications as well as providing an overview of the theory of this increasingly important technique. Renowned experts in the field describe and discuss the latest PCR platforms, fluorescent chemistries, validation software, data analysis, and internal and external controls. This timely and authoritative volume also discusses a wide range of RT-PCR applications including: clinical diagnostics, biodefense, RNA expression studies, validation of array data, mutation detection, food authenticity and legislation, NASBA, molecular halotyping, and much more. An essential book for all laboratories using PCR."--BOOK JACKET.
TOC
Includes bibliographical references and index.
CSE
Sagar Shahanawaz
Keywords: Polymerase chain reaction; Polymerase Chain Reaction -- methods